Laparoscopic Management of a Complex Adrenal Cyst - Koichi Kodama; Yasukazu Takase; Susumu Niikura; Akiko Shimizu; Hiroki Tatsu; Katsuhiko Saito (Case Reports in Urology)
Adrenal cysts are rare, and their clinical management remains controversial. We report a case involving an adrenal cyst with a complicated appearance on radiological studies. Unenhanced computed tomography revealed a unilocular, noncalcified, hypoattenuating mass with a thin wall in the left adrenal gland. The lesion gradually increased in size from 10 to 50 mm at two-year follow-up. On contrast-enhanced magnetic resonance imaging, a mural nodule with contrast enhancement was observed. The entire adrenal gland was excised en bloc via a lateral transperitoneal laparoscopic approach without violating the principles of surgical oncology. The pathological diagnosis was an adrenal pseudocyst. Laparoscopic adrenalectomy is a safe option for the treatment of complex adrenal cysts, while maintaining the benefits of minimal invasiveness.